ECOTYPIC VARIATION IN GROWTH AND SURVIVAL TEMPERATURE OF CLADOPHORA VAGABUNDA (CHLOROPHYCEAE) ISOLATES FROM DIFFERENT CLIMATIC ZONES - Hatta, Agus M.; Breeman, A. M. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1992)
The effect of temperature on relative growth rates (RGR) and the ability to survive at stress temperatures have been investigated in isolates of the green algal species Cladophora vagabunda from Roscoff (Eastern Atlantic, temperate), Corsica (Mediterranean, subtropical), Western Australia (Indian Ocean, subtropical) and Curacao (Western Atlantic, tropical). Growth was observed between 1O°-35°C, except in the Roscoff isolate which grew between 10°-30°C and a temperature of 5°C was too low for growth in all isolates. Those indicate that all isolates were comparatively eurythermal. Variations in RGR were observed with a high maximum RGR in the W. Australian and Roscoff isolates with ca. 74% increase in length per day at 30°C, and a lower maximum RGR in the Corsican and Curacao isolates with ca. 30-50% increase in length per day at 20°-25°C. The broadest optimum range (between 15°-30°C) was shown by the Corsican isolate and the narrowest optimum range (between 25°-30°C) by the Curacao isolate. At a low stress temperature of 0°C, all isolates survived for at least 30 days without damage, after 30-50 days the Roscoff and Curacao isolates showed damage (cell bleaching) but they recovered at 20°C. The W. Australian and the Corsican isolates survived undamage for 60 days. At a high stress temperature of 35°C, the W. Australian and the Curacao isolates survived for 60 days, but the other two isolates died within 30 days. The different temperature responses of the isolates demonstrated the ability of Cladophora vagabunda to exist in varied temperature environments.